Cómo influye la red social TikTok en los adolescentes de 14 a 18 años del cantón Guayaquil - Vinces Alcívar, Vicente Moisés (2024)
In the last decade, social networks have become a fundamental communication tool for people, especially for young people and/or teenagers, since it provides a series of entertainment options. As Macias (2023) points out, in the time of the pandemic, a large rate of downloads emerged worldwide from various social networks and entertainment platforms, with TikTok being the one with the greatest impact on minors. The main objective of this paper is to analyze the influence and contribution of TIKTOK in the cultural and communicational context of adolescents aged 14 to 18 years. For this, the mixed-type approach was used, and information was collected through surveys directed at 22 parents, 118 students and interviews with 4 specialists. Among the main results, it was known that 33% of young people spend their free time browsing social networks, 58% use TIKTOK and the most searched content are jokes/jokes, news, stories, current issues, 80% of the children do make content that is uploaded to the platform and 63% establish that TIKTOK does contribute positively to their academic performance. It was evidenced that 82% of parents are aware that their children use TIKTOK and 73% have not noticed changes in their children's behavior. On the other hand, specialists highlight those serious negative effects on children have been evidenced using cellular devices where they show mental health problems, decreased capacity for executive brain functions, hypersexualization, decreased motor and social skills. Finally, the specialists emphasize that parents should talk openly about the issue by establishing mutual agreements. In this sense, as responsible adults they must recommend content that is appropriate and raise awareness to our young people about the correct use of social networks and their impact on society.